Sports injury research - Verhagen, Evert, 1976-; Van Mechelen, Willem (Oxford : Oxford University Press, 2010)
This text presents a comprehensive guide to the epidemiology and methodology involved in sports injury research, including detailed background on epidemiological methods employed in research on sports injuries and discussions on key methodological issues.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Sports injuries -- Research -- Methodology